2016
DOI: 10.1016/j.ajog.2015.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of pravastatin used for the prevention of preeclampsia in high-risk pregnant women: a pilot randomized controlled trial

Abstract: Background Preeclampsia complicates approximately 3% to 5% of pregnancies and remains a major cause of maternal and neonatal morbidity and mortality. It shares pathogenic similarities with adult cardiovascular disease as well as many risk factors. Pravastatin, a hydrophilic, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitor, has been shown in preclinical studies to reverse various pathophysiological pathways associated with preeclampsia, providing biological plausibility for its use for preeclampsia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 222 publications
(235 citation statements)
references
References 38 publications
11
213
2
9
Order By: Relevance
“…Another recent study has shown that pravastatin stabilized clinical and biochemical features of PE in 4 women (32). Statins have been shown not to be teratogenic as demonstrated by several studies (33,34). A study by Costantine et al reported no identifiable safety risks associated with pravastatin use in a pilot randomized trial designed to determine pravastatin safety and pharmacokinetic parameters in pregnant women at high risk of PE (33).…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study has shown that pravastatin stabilized clinical and biochemical features of PE in 4 women (32). Statins have been shown not to be teratogenic as demonstrated by several studies (33,34). A study by Costantine et al reported no identifiable safety risks associated with pravastatin use in a pilot randomized trial designed to determine pravastatin safety and pharmacokinetic parameters in pregnant women at high risk of PE (33).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these characteristics, recent transplacental studies have shown that the drug's ability to cross the placenta was limited and clearance was higher in the fetal-to-maternal direction than the maternal-to-fetal direction (18). The US randomized controlled trial additionally showed that renal clearance of pravastatin is higher in pregnancy compared with in the nonpregnant state, adding uncertainty to the ideal dose with the safest profile to be used in high-risk pregnant women (15). Data from pregnancy exposure cohorts do not support the teratogenicity claims of pravastatin (6, 19).…”
Section: Statins For Treatment Of Preeclampsia And/or Iugr In Women Wmentioning
confidence: 52%
“…Importantly, the US trial demonstrated an improved angiogenic profile with the use of pravastatin and no difference in the rate of adverse events (based on clinical and laboratory observations) or congenital anomalies. Although pravastatin reduced maternal cholesterol concentrations, umbilical cord cholesterol concentrations and infant birth weight were not different between the treatment and control groups (15).…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations